A new decontamination method for Bacillus subtilisin pasteurized milk: Thermosonication treatment. (January 2023) - Yang, Shanshan; Piao, Yuqiong; Li, Xinfei; Mu, Delun; Ji, Shuaiqi; Wu, Rina; Wu, Junrui
Graphical abstract: Highlights: Thermosonication treatment had a significant decontamination effect on Bacillus subtilis in milk culture media. The cell structure of Bacillus subtilis was damaged by thermosonication. Thermosonication treatment caused leakage of the DNA and protein contents of Bacillus subtilis . The activities of ATPase and dehydrogenase in Bacillus subtilis were inhibited by thermosonication. Thermosonication decontamination is a feasible and effective method for improving the quality and shelf life of pasteurized milk products in the future. Abstract: Thermosonication (TS) is a novel and viable technique employed to replace conventional thermal processing. TS treatment combined with pasteurization was used to kill the residual heat-resistant Bacillus in pasteurized milk and extend the shelf life of pasteurized milk and compared with High Temperture Shoort Time (HTST) pasteurization to study its decontamination effect on Bacillus subtilis and the quality of treated milk. The results showed that after 40 kHz, 240 W, 25 min ultrasonic treatment and 50 °C heating decontamination treatment, the number of B. subtilis in the medium and milk medium decreased by 4.17 log CFU/mL and 4.09 log CFU/mL respectively. The results of cell membrane permeability showed that the leakage of DNA and protein in the HTST-TS group increased by 52.3 % and 34 %, respectively, when compared to that in the HTST group. In addition, transmission electron microscopy (TEM) analysis showed that the bacterial cell membrane of the HTST-TS group swelled up, the cell wall was ruptured, and the cell content was accumulated in the cells. The results showed that HTST-TS treatment significantly inhibited the activities of ATPase (47 %), succinate dehydrogenase (SDH) (68.6 %), and malate dehydrogenase (MDH) (54.4 %). The physical and chemical sensory evaluation of milk treated with HTST-TS showed that HTST-TS treatment could improve the L* value (2.24 %), zeta potential (64.19 %), and colloidal particle size (14.49 %) of milk but had no significant effect on oral sensitivity. In conclusion, this study provides new insights, which may be helpful in implementing this new combined decontamination method in the dairy industry to improve the quality of pasteurized milk and extend the its shelf life.